STRUCTURAL AND FUNCTIONAL CHANGES OF MYOCARDIUM IN WOMEN WITH OSTEOPOROSIS IN COMBINATION WITH ISCHEMIC HEART DISEASE - S. Yu. Tsarenok (Klinicist)
The aim of our study was to determine the characteristics of structural and functional changes of myocardium and aorta by echocardiography in women with ischemic heart disease (IHD) cause-specific from the presence of osteoporosis.Materials and methods. We examined 170 postmenopausal women aged from 57 to 78. Inclusion criteria: female gender, age over 50 years, the presence of menopause, the presence of IHD. Exclusion criteria: endocrine system diseases, severe heart failure, respiratory insufficiency, secondary osteoporosis. Postmenopausal osteoporosis was diagnosed according to the Clinical Recommendations for the Prevention and Management of Osteoporosis Patients (2016). All women were divided into 2 groups: group 1 – 72 women with proven diagnosis of osteoporosis and IHD, group 2 – 98 patients with isolated IHD (comparison group). IHD was represented by 2 forms: angina pectoris and postinfarction cardiosclerosis. The frequency of postinfarction cardiosclerosis was not statistically different between groups. Also the groups were comparable in age, weight, body-weight index, levels of peripheral (office) blood pressure.Results. In women with osteoporosis and IHD we revealed higher values of interventricular septum thickness (p = 0.034), left ventricle posterior wall (p = 0.004), and the relative thickness of left ventricular posterior wall (p = 0.0038). An increasing rate of left ventricular hypertrophy was observed in patients with combination of osteoporosis and IHD – 51.4 % versus 39.8 % in women with IHD without osteoporosis (p = 0.002). Osteoporosis was associated with a higher incidence of diastolic left ventricular dysfunction: 90 % versus 70.4 %, as well as with pathological types of left ventricular remodeling (p = 0.01); concentric remodeling type dominated among women with combined pathology (p = 0.09). A higher incidence of aorta calcification 1.86 times (p = 0.00013) and calcified aortic stenosis (13.8 % versus 4.08 %; p = 0.02) were noted in patients with osteoporosis.Conclusion. We found that osteoporosis in postmenopausal women was associated with an increasing of heart remodeling parameters, an increasing of diastolic dysfunction frequency and pathological types of left ventricle geometric remodeling with prevalence of concentric type remodeling. Patients with osteoporosis had a higher prevalence of aortic calcification and calcified aortic stenosis.